Você já blogou hoje? Um estudo de caso sobre o uso de blogs nas aulas de Língua Inglesa - GONÇALVES, Rejane Maria (2009)
This study aims to verify that so the blog is used in English class, identifying the types of interactions that occur during the construction and development of blogs and how they can contribute to the teaching and learning of English as LE / L2. This research was guided by two main theoretical axes: sociocultural theory, which addresses the importance of interaction for the development of learning and Information Technology and Communication, with emphasis on computer and Internet use in the classroom in LE/L2. Our research is qualitative and is configured as a case study. It was developed in a class of 16 students of Letrasde a public university in the state of Goiás, during the second half of 2008. The data discussed were obtained through a questionnaire, interviews, classroom observation with field notes, recording audio and video interactions, written reflection and students' blogs. Data analysis allowed us to identify moments of classroom interaction during which the students negotiated meaning, form and content, as well as offered and received scaffoldings. The virtual space was also used as a place of socio-emotional and cognitive development among participants. These results show the blog as a tool to motivate students and providing them with autonomy in learning LE/L2